FINRA regulation: new fixed-income research rule, modifications to equity research rule, and FAQ on conflicts of interest in offering process. Issue 1 (3rd May 2016) - Sacks, Russell D.; Blau, Steven R.; Nishide, Taro
Abstract : Purpose: To address practical issues broker-dealers may face in reviewing and revising their policies and procedures in response to FINRA's new fixed-income research rule, modifications to its equity research rule, and its FAQs regarding conflicts of interest in the offering process. Design/methodology/approach: Reviews FINRA's new fixed-income research rule, modifications to its equity research rule, and its FAQs regarding the its equity research rule, and provides detailed comparisons between current rules and new rules to help firms consider how to review and revise their policies and procedures. Findings: Although significant exemptions may apply depending on firm structure, under FINRA's new fixed-income research rule, firms producing fixed-income research reports will now be subject to regulation similar to that FINRA has imposed on firms producing equity research reports, including with respect to information barriers, other policies and procedures, and certain disclosures. The modified FINRA equity research rule retains the core provisions of the existing NASD and NYSE equity research rules and adds a "principles-based procedures" approach to potential conflicts of interest, shortens or eliminates quiet periods, and imposes some of the Global Settlement prohibitions on all firms. Firms will need to review and revise their policies and procedures for research in response to these rule changes. Firms should also take note of FINRA's guidance in its FAQs regarding conflicts of interest in the offering process. Originality/value: Overview of recent FINRA enforcement activity, rule modifications, and practical guidance from experienced securities and financial services lawyers.